Al-Jalalain Tafsir Study (Living Qur'an Study at Al-Muqri As-Salafi Islamic Boarding School) - Izzatul Ummah; Abdul Muiz (Penerbit Hellow Pustaka, 2025)
The majority of the Salafiyah boarding schools in Madura make the book of Tafsir Al-Jalalain as the main study of the Qur'anic interpretation book. It is hoped that later on this book of interpretation will be a provision and a reference for the santri when they immerse themselves in the community for the development of Islam. One of the many Salafiyah pesantren in Madura that makes Tafsir Al-Jalalain as the main study of the interpretation book is Al-Muqri Assalafi Islamic Boarding School. Interestingly, although this pesantren is relatively small, the study of Tafsir Al-Jalalain is still maintained from generation to generation. The purpose of this research is to find out the background and methods used in the study of Tafsir Al-Jalalain at the Al-muqri Assalafi Islamic Boarding School. While the research method used is a descriptive qualitative approach. With the type of field research. Data collection techniques using observation, interviews with caregivers, administrators and 6 students who follow the tafsir study. The results of this study show that the background of the study of tafsir jalalain is the Sanad of the caregiver, tafsir jalalain is more quickly understood because of its simple language. The method used in the study of tafsir jalalain at Al-Muqri Assalafi Islamic Boarding School is the bandongan method.